A global perspective on national climate mitigation priorities in the context of air pollution and sustainable development. (September 2019) - Liu, Qingyang; Baumgartner, Jill; de Foy, Benjamin; Schauer, James J.
Abstract: Air pollution and climate change are key global challenges for cities and both have large impacts on human health and economic development. Although there are many long term opportunities to address these issues with integrated policies, the immediate needs of addressing air pollution and climate change mitigation are not the same for all countries in the short run. We examined the relationships between greenhouse gases (GHG) emissions, outdoor air pollution, and levels of socioeconomic development to identify specific near-term mitigation policy responses to climate change and air pollution for countries with different levels of human development. Human development index, as defined by The United Nations Development Programme (UNDP) is a measure of achievement in the basic dimensions of human development across countries, which combines the gross national income index, an education index and a life expectancy index (http://hdr.undp.org/en/humandev ). Country-level data were collected on indicators of socioeconomic development, emissions of GHG, and outdoor levels of fine particulate matter (PM2.5 ) from the World Bank, the UNDP, and the Task Force on Hemispheric Transport of Air Pollution. Differences in GHG emissions and air pollution concentrations, as well as socioeconomic development indicators, were assessed at national, sub-national, and global scales. Countries were divided into four categories based on CO2 emissions per capita and an estimation of outdoor PM2.5 : Group A was characterized by high CO2 emissions per capita and low PM2.5 concentrations, Group B by high CO2 emissions per capita and high PM2.5 concentrations, Group C by low CO2 emissions per capita and low PM2.5 concentrations, and Group D by low CO2 emissions per capita and high PM2.5 concentration. Per-capita emissions of CO2 were strongly correlated with the level of socioeconomic development, while differences in non-CO2 greenhouse gas emissions per capita across the groups were not correlated. Atmospheric PM2.5 concentrations were not correlated with either CO2 emissions per capita or levels of socioeconomic development. Energy and environmental policies focused on CO2 emission reductions may not inherently lead to development pathways that sufficiently reduce population exposure to air pollution. Countries with low CO2 and high air pollution levels should pursue short-term policies to reduce air pollution and increase human development, beginning to address GHG emissions after critical human health and development needs are met. Highlights: 184 countries were grouped into four categories based on the CO2 emissions per capita and PM2.5 . Countries with low CO2 and high air pollution levels should reduce air pollution and increase human development in short run. Countries with high CO2 and high air pollution levels should pursue short-term policies to reduce air pollution. Countries with low CO2 and low air pollution levels should increase human development near short-term.